Green synthesis of gold and silver nanoparticles using crude extract of Aconitum violaceum and evaluation of their antibacterial, antioxidant and photocatalytic activities - Ahmad, Shahbaz; Ahmad, Shujaat; Xu, Qianqian; Khan, Idrees; Cao, Xiaoyu; Yang, Ruimin; Yan, Hai (Frontiers in Bioengineering and Biotechnology, 2024)
Green synthesis of metal nanoparticles (NPs) has received extensive attention over other conventional approaches due to their non-toxic nature and more biocompatibility.Herein we report gold and silver NPs (AuNPs@AV and AgNPs@AV) prepared by employing a green approach using crude extract of Aconitum violaceum Jacquem. ex Stapf. The synthesized NPs were characterized using Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), Energy Dispersive X-ray (EDX), X-ray Diffraction (XRD), UV/Visible spectroscopy, Fourier Transform Infrared (FTIR), X-ray Photoelectron Spectroscopy (XPS), and Zeta Potential. Morphological analysis showed spherical and triangular shapes of the NPs with average size of >100 nm. The AuNPs@AV and AgNPs@AV exhibited effective antibacterial activities, with minimum inhibitory concentrations (MICs) of 95 and 70 μg/ml against Lactobacillus acidophilus (L. acidophilus) and 90 and 65 μg/ml against Escherichia coli (E. coli), respectively. Strong antioxidant effect of AuNPs@AV and AgNPs@AV were reported against DPPH radical and PTIO within range of IC50 values; 161-80 μg/ml as compared to the standard (23-11 μg/ml) respectively. Moreover, the AuNPs@AV and AgNPs@AV showed efficient photocatalytic activity and degraded 89.88% and 93.7% methylene blue (MB) dye under UV light, respectively.